Ring walking as a regioselectivity control element in Pd-catalyzed C-N cross-coupling - Madeleine C. Deem; Joshua S. Derasp; Thomas C. Malig; Kea Legard; Curtis P. Berlinguette; Jason E. Hein (Nature Communications, 2022)
The phenomenon of „ring-walking‟, wherein a metal catalyst remains bound to a pi system as it migrates to another coupling site, is supported largely by circumstantial evidence. Here the authors perform an in-depth kinetic study of Buchwald- Hartwig animations with several catalytic systems delineating the phenomenon of ring walking from diffusion-controlled coupling.